Responsiveness of urogynecologic quality of life measurements to change after radical gynecologic surgery - (:unkn) unknown (SPRINGER HEIDELBERG, 2011)
In order to assess the responsiveness of short forms of the Incontinence Impact Questionnaire (IIQ-7) and Urogenital Distress Inventory (UDI-6) in a subset of women undergoing radical operations for gynecologic cancer. Women with cervical cancer without any abnormal urodynamic abnormalities who had undergone Class III hysterectomy were included in the study. All women underwent urodynamic investigation and completed the IIQ-7 and UDI-6 questionnaires pre-operatively and post-operatively in the sixth month. Twenty-eight patients were enrolled and general and subscale scores of the questionnaire were calculated in the study between February 2008 and September 2008. Class III hysterectomy was performed in 28 women with stage Ib cervical carcinoma. Scores of IIQ-7 and the irritative and obstructive subscales of UDI-6 in the sixth post-operative month were significantly higher than the pre-operative scores. The Cronbach's alpha was 0.84. Cystometric parameters were in concordance with these changes in the questionnaire scores. The IIQ-7 and UDI-6 questionnaires are sensitive to changes in patients who have undergone radical oncologic operations because their life impact of incontinence may be affected. Validated questionnaires are reasonable measures to detect these changes, which are confirmed by urodynamic findings.
Keywords: Radical surgery; Quality of life; Urodynamics; INCONTINENCE IMPACT QUESTIONNAIRE; UROGENITAL DISTRESS INVENTORY; CERVICAL-CANCER; URINARY-INCONTINENCE; SHORT FORMS; HYSTERECTOMY; WOMEN; DYSFUNCTION; SYMPTOMS